2009
DOI: 10.1111/j.1532-5415.2008.02170.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Screening of Cognitive Change in Patients with Questionable Dementia Using the Memory Impairment Screen and the Isaacs Set Test

Abstract: This quickly performed tool (5 minutes) is simple to use and score. When including cutscores (MIS<6 or IST<25) or range values, this test could be considered a useful screening procedure for all types of dementias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The mental control subtest of the Wechsler Memory Scale combined with RAVLT delayed recall was shown to have a classification accuracy of 89% in memory-impaired non-demented patients, two years before AD diagnosis [30]. Similarly, high predictive accuracy was found when combining episodic memory with naming [38,39] or verbal fluency [27,40,41]. Particularly high prediction values were obtained when combin-ing memory with more than one other domain.…”
Section: Cognition In Preclinical Admentioning
confidence: 96%
“…The mental control subtest of the Wechsler Memory Scale combined with RAVLT delayed recall was shown to have a classification accuracy of 89% in memory-impaired non-demented patients, two years before AD diagnosis [30]. Similarly, high predictive accuracy was found when combining episodic memory with naming [38,39] or verbal fluency [27,40,41]. Particularly high prediction values were obtained when combin-ing memory with more than one other domain.…”
Section: Cognition In Preclinical Admentioning
confidence: 96%
“…Using the discrete Cox proportional hazards model, Dartiques et al (1997) found the IST to be a better test to predict the development of dementia when compared with the MMSE and BVRT. Chopard et al (2009) found that combining the IST and the MIS resulted in an AUC of 0.86 which was superior to the MMSE (AUC = 0.59). Tang-Wai et al (2003) determined the STMS to be significantly better than the MMSE in discriminating between the four different diagnostic groups in the study.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of answers to the QUADAS items were "yes", and nine studies obtained perfect scores. Three studies (Chopard et al, 2009 ;Larner, 2007 ;Tsukamoto et al, 2009 ) had answers of "no" to one or two of the items. Questions 3 to 11 of the QUADAS tool referred to an index test and reference standard.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…El "Memory Impairment Scren" (MIS) (Buschke et al, 1999) es un test que permite evaluar la memoria episódica verbal (recuerdo libre y facilitado de una lista de 4 palabras que el sujeto puede leer) por su contenido viene a ser una prueba muy rápida con una duración de 4-5 minutos (Böhm et al, 2003;Buschke et al, 1999), y pudiéndose aplicar a cualquier tipo de demencia (Chopard et al, 2009). En el caso de la versión española, los autores proponen al MIS como una prueba fiable para diferenciar entre sujetos con demencia Alzheimer, obteniendo índices diagnósticos adecuados (S=0.86 y E=0.96; aROC= 978) y apto como primer instrumento de detección (Böhm et al, 2005).…”
Section: "Memory Impairment Scren" (Mis)unclassified